Evaluation of granular-activated carbon-attached biofilm coated in alginate-chitosan for biohydrogen production - Dzul Rashidi, Nur Farahana (2022)
Biohydrogen production via an anaerobic dark fermentation process at thermophilic conditions is recognized as an excellent biological method and more cost-effective due to its ability to perform without light energy and oxygen source. At thermophilic, this research aims to investigate the effect of bacterial immobilization on a matrix made of alginate and chitosan co-polymerization towards biohydrogen production. In the first objective, the effect of hydrogen production using granular activated carbon (GAC) as a microbial support carrier in forming GAC-attached biofilm was evaluated based on different amounts of sugar concentration as microbial feedstock. The comparison between initial sugars loading was conducted in a water bath shaker at 120rpm in 800 ml working volume. The acclimatization was operated in a sequencing batch system at a thermophilic temperature of 60oC and the initial feedstock was set at pH 6. The fermentation process was continuously carried out until a steady state of biogas was obtained and it showed the attached-biofilm system successfully stabilizing hydrogen production after 40 days. The second objective involved the entrapment process in the formation of GAC-attached biofilm using alginate and chitosan as carrier polymers in the form of beads. Bacterial immobilization was done by entrapment of GAC-attached biofilm into 0.5g,1g,2g,3g and 4g of alginate and chitosan respectively (GAC-Alg and GAC-AlgC). The immobilized beads for both alginate and chitosan were conducted in batch fermentation using a synthetic medium at a temperature of 60°C, pH 6.0 and in 200 ml working volume. The entrapment of GAC-attached biofilm provides good support for microorganisms to grow and colonize where high bacterial loads were observed under a scanning electron microscope (SEM). Lastly, in the final objective, this research was conducted to assess the performance of GAC-Alg and GAC-AlgC immobilized beads by using POME as a fermentation medium. It has been observed that the GAC-Alg immobilized beads resulted in stable hydrogen production after 52 hours with a consistent HPR of 1.02 mmol H₂/l.h and 1.83 mmol H2/l.h for GAC- AlgC. Overall, this study showed the immobilization of bacteria-entrapped beads promising approach to protect the bacteria colonization during the fermentation, thus retaining and promoting microbial growth and protecting the microbial from an unfavourable environment.